2019
DOI: 10.1038/s41598-019-53658-5
|View full text |Cite
|
Sign up to set email alerts
|

Endemic foot and mouth disease: pastoral in-herd disease dynamics in sub-Saharan Africa

Abstract: Foot and mouth disease (FMD) burden disproportionally affects Africa where it is considered endemic. Smallholder livestock keepers experience significant losses due to disease, but the dynamics and mechanisms underlying persistence at the herd-level and beyond remain poorly understood. We address this knowledge gap using stochastic, compartmental modelling to explore FMD virus (FMDV) persistence, outbreak dynamics and disease burden in individual cattle herds within an endemic setting. Our analysis suggests re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 58 publications
0
14
0
1
Order By: Relevance
“…FMD outbreaks in endemic regions can be expected to follow a cyclical pattern, depending on control strategies, of approximately 3–7 years with consecutive annual outbreaks most likely due to different serotypes (Aman et al., 2020; Gallego et al., 2007; McLachlan et al., 2019). Currently, serotypes O and A are known to be circulating in Laos with typed outbreaks reported in 2018 (OIE, 2020); Asia1 has not been detected in South East Asia since 2007 (Blacksell et al., 2019; Brito et al., 2017; King et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…FMD outbreaks in endemic regions can be expected to follow a cyclical pattern, depending on control strategies, of approximately 3–7 years with consecutive annual outbreaks most likely due to different serotypes (Aman et al., 2020; Gallego et al., 2007; McLachlan et al., 2019). Currently, serotypes O and A are known to be circulating in Laos with typed outbreaks reported in 2018 (OIE, 2020); Asia1 has not been detected in South East Asia since 2007 (Blacksell et al., 2019; Brito et al., 2017; King et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, herd immunity due to a recent previous outbreak may decrease the risk of a subsequent outbreak, particularly from a similar strain of the virus as the outbreaks in 2016 and previous year were from the same serotype (Serotype O). A previous study also indicated that the risk of further outbreaks of the past outbreak herd was reduced due to individual immune [39].…”
Section: Discussionmentioning
confidence: 92%
“…modelling FMD in epidemic settings (Björnham et al, 2020;Ferguson et al, 2001;Hayama et al, 2013;Kao, 2002;Keeling, 2001;Schley et al, 2009;Tildesley et al, 2008;Wada et al, 2017); however, relatively few studies have looked at FMD in endemic settings (Kim et al, 2016;McLachlan et al, 2019;Pomeroy et al, 2017;Ringa et al, 2014;Schnell et al, 2019). Of these, only…”
Section: Parameter Valuesmentioning
confidence: 99%